Cara Meningkatkan Kemampuan Bacaan Al Qur’an Melalui Metode Baghdadiyah Di Kelas VIII-1 SMP Al Washliyah 30 Medan - Munawir Pasaribu; Syafira Ayu Armadhy Putri (Jurnal Masyarakat Indonesia (Jumas), 2022)
This research was conducted at Al Washliyah Junior High School 30 Medan which aims to improve the ability to read the Qur'an through the introduction of hijaiyyah letters using baghdadiyah method in class VIII-1 Al Washliyah Junior High School 30 Medan. This type of research is classroom action research. The approach is a qualitative and quantitative approach that leads to an increase in the ability to read the Quran through Baghdadiyah methods. The instruments used in this study are in the form of tests, observation sheets and documentation. This research consists of three cycles,consisting of four stages, namely planning, implementation, observation, reflection, also accompanied by discussion. The subject of the researchers of this study were students of class VIII-1 Al Washliyah Junior High School 30 Medan which amounted to 20 people. The results of this study showed that there was an increase in the reading ability of the Quran of learners through the Baghdadiyah method in Al Washliyah Junior High School 30 Medan, in the initial condition (precycle) by 31.25%, increased in cycle I to 42.5%, in cycle II the reading ability of learners increased to 66.25% and in cycle III increased to 82.50%.Â